Long-term experience of the thermo-active ground source system at the metro station Taborstrasse in Vienna - Dietmar Adam; Adrian Brunner; Roman Markiewicz; Johannes Pistrol (Acta Polytechnica CTU Proceedings, 2023)
Four of the stations newly opened during the underground extension of the U2 line in Vienna in 2008 have been covering a large part of their heating and cooling needs for now almost one and a half decades by using geothermal energy, which is generated by means of energy diaphragm walls, energy piles and energy bottom slabs of the station buildings. As this was the first infrastructure building of this type and scale worldwide at the time of construction, one of the diaphragm walls of the Taborstraße station was equipped with numerous sensors to obtain data sets for the thermo-mechanical long-term behavior of these wall elements for the very first time. Continuous measurements with automatic data recording were initially carried out from April 2008 until May 2011. In October 2020, the measurements were resumed with the existing sensors, this time manually and once a month, in order to carry out a long-term comparison of the measurement data and to create a basis for assessing the effects of the geothermal operation on its structural components. This paper gives an overview of the Taborstraße station with a focus on the thermally activated geostructures and their instrumentation. A comparison of the recorded generated energy with the predicted heating and cooling demand is discussed in the context of the energy data. In addition, the temperature and the strain behavior of the observed energy diaphragm wall is discussed based on the measurement data collected over a period of around 14 years of operational experience.